Ecologically restoring brownfields in urban coastal zones: a case for South Providence, Rhode Island - Killinger, Mary Katheryn (Kansas State University, 2024)
Coastal brownfields are a critical issue in coastal areas, especially in port and post-industrial cities. There have been many studies conducted on the redevelopment of brownfields. However, there are limited reports covering both short-term solutions and long-term ecological restoration of sites in coastal brownfields. This study explores the feasibility and potential of restoration strategies for a coastal brownfield in the short and long term. The Port Area of South Providence, RI, is the focus of the study as it is a typical post-industrial city with ecological problems resulting from coastal brownfields. The proposed project consists of two phases: research and design phases. First, the research phase includes coastal brownfield literature analysis, expert surveys, and interviews with local experts in Providence. The research phase aims to create a framework to synthesize coastal brownfield restoration strategies at different site scales and restoration timeframes. Second, the design phase includes site analysis, precedent studies, and projective design. The design phase aims to develop a proposal for a short-term site-scale coastal brownfield restoration and a long-term ecological restoration at an urban scale. The outcomes are a multiphase conceptual master plan with short-term and long-term ecological restoration solutions and design works for brownfield restoration. The study’s outcomes contribute to the discussion of the ecological restoration of coastal brownfields and can be utilized as a reference for other landscape architects, urban designers, brownfield experts, and city planners.
Keywords: Coastal brownfield; Coastal restoration; Brownfield redevelopment; Coastal infrastructure; Coastal flooding; Climate change